2003
DOI: 10.1016/s0960-9822(03)00244-6
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Lgl Forms a Protein Complex with PAR-6 and aPKC Independently of PAR-3 to Regulate Epithelial Cell Polarity

Abstract: These results indicate that PAR-6/aPKC selectively interacts with either mLgl or PAR-3 under the control of aPKC activity to regulate epithelial cell polarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
357
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 321 publications
(378 citation statements)
references
References 42 publications
19
357
1
1
Order By: Relevance
“…Earlier studies have demonstrated that the several closely spaced, highly conserved phosphorylation sites in the central linker region of Lgl2 can be phosphorylated by aPKC both in vivo and in vitro [16][17][18][19] (Figure 1A). Although phosphorylation is believed to be important for the proper function of Lgl2, how the phosphorylation of Lgl2 affects its function is still unclear.…”
Section: The Phosphorylation-dependent Interaction Between Lgl2 and Dmentioning
confidence: 91%
“…Earlier studies have demonstrated that the several closely spaced, highly conserved phosphorylation sites in the central linker region of Lgl2 can be phosphorylated by aPKC both in vivo and in vitro [16][17][18][19] (Figure 1A). Although phosphorylation is believed to be important for the proper function of Lgl2, how the phosphorylation of Lgl2 affects its function is still unclear.…”
Section: The Phosphorylation-dependent Interaction Between Lgl2 and Dmentioning
confidence: 91%
“…Par3, Par6, and aPKC form an apical protein complex (reviewed in Etienne- Manneville and Hall, 2003). Formation of this complex controls microtubule organization and excludes basolateral proteins, such as Lethal giant larvae (Lgl), from the apical membrane by direct aPKC-mediated phosphorylation (Plant et al, 2003;Yamanaka et al, 2003). Disruption of the apical protein complex or inhibition of aPKC function prevents formation of a functional apical domain and ultimately disrupts apical/ basal polarity.…”
Section: Molecular Regulation Of Te Vs Icm Fate Choicementioning
confidence: 99%
“…Although it is possible that NMHC II-B serves as a downstream target of aPKC in regulating cell adhesion in the spinal canal, there are other putative targets in the neuronal adherens junction as well, such as PAR3 and Lgl1 (Yamanaka et al, 2003;Klezovitch et al, 2004;Suzuki and Ohno, 2006;Vasioukhin, 2006). In contrast, Even-Faitelson and Ravid (2006) have reported that phosphorylation of the NMHC II-B in the nonhelical tail by an aPKC results in cortical localization of both NM II-B and aPKC in a prostate cancer cell line.…”
Section: Cell-cell Adhesion Of the Neuroepithelial Cells Requires Nonmentioning
confidence: 99%